Quantifying blue carbon stocks in interconnected seagrass, coral reef, and sandy coastline ecosystems in the Western Gulf of Thailand - Yeemin, Thamasak; Sutthacheep, Makamas; Pengsakun, Sittiporn; Klinthong, Wanlaya; Chamchoy, Charernmee; Suebpala, Wichin (Frontiers in Marine Science, 2024)
Coastal and marine ecosystems play a major role in the global carbon cycle. Connected marine and coastal ecosystems are commonly observed in the Western Gulf of Thailand. Little is known about the blue carbon potential of these interconnected ecosystems and seascapes. This study aims to quantify blue carbon stocks in the interconnected seagrass-coral reef-sandy coastal ecosystems at Samui Island, the Western Gulf of Thailand. At each study site, the samples of seagrasses, algae, and sediments, were collected from the different zones along a transect of interconnected sandy beach-seagrass bed-coral reef habitats, and the organic carbon contents were quantified using elemental analysis and loss on ignition (LOI). Our findings indicate that the habitats may provide a potential blue carbon opportunity. With a total area of 178.04 hectares (ha), consisting of sand (47.70 ha), seagrass beds (122.44 ha), macroalgal beds (2.40 ha), and live corals (5.50 ha), the estimated carbon storage was as much as 9,222.75 MgC; 74.03% of which was stored in sediment, while the rest was as biomass (25.97%). About 96 percent of the total carbon storage was found in seagrass beds (122.44 ha) with a total amount of carbon storage of 8,876.99 MgC, consisting of 8,781.01 MgC and 95.98 MgC of shallow- and deep-seagrass beds, respectively. The carbon stocks in seagrass, algal biomass, and sediment ranged from 1.58 - 19.10 MgC.ha-1, 2.51 -10.45 MgC.ha-1, and 0.93 - 58.46 MgC.ha-1, respectively. Comparing the carbon storage at each study site, Ko Tan showed the highest value of carbon storage, accounting for 4,232.21 MgC, followed by Ao Phangka (2,901.83 MgC), Ao Thong Tanod (1,459.57 MgC) and Ko Mudsum (629.14 MgC). The quantities of carbon stocks varied considerably among microhabitats and the connectivity of these coastal and marine ecosystems may support the carbon stocks potential of the interconnected ecosystems. Ultimately, the findings from this study provide baseline data that supports Thailand’s nationally determined contribution and highlight the importance of interconnected coastal ecosystems in carbon sequestration and storage that should not be overlooked.